Macroeconomic stabilization, monetary-fiscal interactions, and Europe's monetary union - Giancarlo Corsetti; Luca Dedola; Marek Jarociński; Bartosz Maćkowiak; Sebastian Schmidt (European Central Bank (ECB), 2016)
The euro area has been experiencing a prolonged period of weak economic activity and very low inflation. This paper reviews models of business cycle stabilization with an eye to formulating lessons for policy in the euro area. According to standard models, after a large recessionary shock accommodative monetary and fiscal policy together may be necessary to stabilize economic activity and inflation. The paper describes practical ways for the euro area to be able to implement an effective monetary-fiscal policy mix.
Keywords: E31; E62; E63; 330; eurobond; government bonds; joint analysis of fiscal and monetary policy; lower bound on nominal interest rates; self-fulfilling sovereign default